IMPLEMENTATION OF LOCAL REGULATION IN CENTRAL JAVA NUMBER 6 YEAR 2013 ABOUT POPULATION CONTROL AND IMPLEMENTING FAMILY PLANNING (Study Case Of Family Planning Program In Department Of Population And Family Planning And Womenâs Empowerment And Child Protection) - Winarti, Aris Tri Haryanto, Nisa Nur Aini (Solidaritas, 2018)
ABSTRACTÂ The aim of this research is to describe and analysis about local regulation of central java number 6 year 2013 about population control and implementation policy of family planning program in wonogiri. In case to support this analysis of implementation policy of family planning program , it basically used the theory of model implementation by Van Meter and Van Horn.This research is literally used descriptive qualitative methode. It called purposive sample and snowball technique. Whereas observing, interviewing and documentation is the part of the collection data technique.And the result of this study is generally, the family planning program in Wonogiri is good. But in the other hand, socialization and counseling are not equally handle by department of counseling field of family program. It cause the limited resources in their region. Citizents are generally had the basic socialization by doctor and nurse.Â Keywords: implementation, family planning, socialization.